SISTEM PENDIDIKAN ISLAM - Sajadi, Dahrun (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2021)
Abstrak: (In English) The birth of Islam which was brought by Allah's Apostle, in the 7th century AD, gave rise to an extraordinary driving force, which has been experienced by mankind. Islam is a giant movement that has been running throughout the ages in its growth and development. The entry and development of Islam in Indonesia from a historical and sociological perspective is very complex and there are many problems, especially regarding the history of the early development of Islam. There is a difference between the old opinion and the new opinion. The old opinion states that Islam entered Indonesia in the 13th century AD and the new opinion states that Islam first entered Indonesia in the 7th century AD. Aceh area. The arrival of Islam to Indonesia was carried out peacefully, it can be seen through trade routes, da'wah, marriage, Sufism and tarekat teachings, as well as arts and education, all of which support the rapid process of Islam entering and developing in Indonesia. Islamic education activities in Aceh were born, grew and developed along with the development of Islam in Aceh. The mass conversion of society to Islam during the Islamic kingdom in Aceh could not be separated from the influence of the royal rulers and the role of scholars and poets. Aceh has been the center of Islamic studies since the time of Sultan Malik Az-Zahir, with an informal education system in the form of halaqoh. Which in turn became the formal education system.